Helminth parasites of juvenile green turtles Chelonia mydas (Testudines, Cheloniidae) in Brazil - Werneck, Max Rondon; Silva, Reinaldo José da [UNESP] (American Society of Parasitologists, 2015)
The present study offers a parasitological analysis of juvenile individuals of the green turtle (Chelonia mydas) found on the Brazilian coast between 2004 and 2011. Helminths were found in 90 out of 136 individuals (66.2%, CI= 57.7 - 74.0). In total, 29,411 helminths were collected, belonging to the families Brachycoeliidae, Cladorchiidae, Microscaphidiidae, Pronocephalidae, Rhytidodidae, and Spirorchiidae. Mean species richness was 4.74 (CI= 4.03 - 5.46), the mean intensity was 327 (CI= 223 - 489) the mean abundance was 216 (CI= 146 - 339). This study also reports new geographical records for: Angiodictyum longum, Angiodictyum parallelum, Rameshwarotrema uterocrescens, Pyelosomum cochlear, Schizamphistomum scleroporum, Cymatocarpus solearis and Neospirorchis sp. This is the first analysis of helminths composition in juveniles of green turtles.